Use of egg-yolk antibodies to prevent diarrhoea in weaning pigs - Torrallardona D.; Brufau J. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
A trial was conducted with 24 21day-old piglets to study the effect of their weaning diet supplemented with egg-yolk antibodies. These had been obtained from hens immunised against some pathogenic strains of E. coli. The animals were distributed in eight pens of three animals, and two experimental diets were tested: T-1 (control diet) and T-2 (control diet plus egg yolk antibodies) for 21 days. Before starting the trial, the facilities were not cleaned to increase the possibility of piglets exposure to pathogenic strains of E. coli. Despite the 'dirty' environment, no diarrhoea symptoms appeared during the trial for any treatment. No statistically significant differences were observed between treatments, although piglets offered egg-yolk antibody diets grew and converted feed slightly better than the control group. It can be concluded that egg-yolk antibodies increased only very slightly the pigs performance. In presence of pathological problems however, this effect may have been more evident.
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)